Analisis Sistem Pengarsipan Digital pada PT Java Indoku - Alma Zhafira; Christian Wiradendi Wolor; Eka Dewi Utari (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2025)
The purpose of this research is to find out the digital archive management system, examine the obstacles faced, and evaluate the feasibility of the available facilities. This study uses a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the archiving process at PT Java Indoku is still carried out manually and digitally at the same time without an organized central system. The main obstacles found include the absence of digital archive servers, the lack of clear standards in document storage, limited supporting facilities, and the lack of a strategic plan to implement a comprehensive digital archiving system. Therefore, the implementation of integrated digital archive management is expected to be a solution to increase the effectiveness of business processes and overall company information management.